Validity evidence for using an online peer-assessment tool (CATME) to assess individual contributions to interprofessional student teamwork in a longitudinal team-based learning course. Issue 6 (2nd November 2022) - Earnest, Mark; Madigosky, Wendy S.; Yamashita, Traci; Hanson, Janice L.
ABSTRACT: Assessing competence for teamwork is a challenging task. Neverthesless, health professions training programs are asked to assure collaborative competency in their learners. Interprofessional education (IPE) programs seek tools to assess team member effectiveness and demonstrate collaborative competency. The Comprehensive Assessment of Team Member Effectiveness (CATME), originally developed for use in engineering, has been applied in various learning settings, with limited use in IPE. This paper presents validity evidence in 4 domains (content, response processes, internal structure, and relations to other variables) for the use of the CATME in a classroom-based IPE course taught with Team-Based Learning.